Pengaruh Profitabilitas dan Biaya Operasional Terhadap PPh Badan Industri Makanan dan Minuman - Setianingrum, Helvy Fatima; Hanifa, Nurul (Jurnal Ekonomika : INDEPENDEN, 2025)
This study aims to analyze the impact of profitability and operating expenses on corporate income tax in the food and beverage industry listed on the Indonesia Stock Exchange from 2019 to 2023. The researcher employs a quantitative approach using panel data regression analysis. The study utilizes secondary data, specifically panel data derived from financial reports of relevant companies available on the IDX website. The findings indicate a significant positive effect of the Net Profit Margin (NPM) ratio, representing profitability, on corporate income tax. Similarly, operating expenses also exhibit a significant positive impact on corporate income tax. Overall, both NPM as a profitability ratio and operating expenses collectively have a significant influence on corporate income tax.